Legal implications of framing the legislative basis of vegetation protection - Соколова, А. К. (Problems of legality, 2014)
We have launched the study of problem, related to determining the legal basis of protecting the flora objects with specification of its legal implications. Aim of the publication is to clarify the structure and dynamics of the legislation within 1917 - 1990 related legal relations as regards of protection, use and reproduction of vegetation.